KREATIVITAS TUTOR DALAM MENINGKATKAN MOTIVASI BELAJAR WARGA BELAJAR DI PKBM AMANAT UMMAT - Faradilla Faradilla; Suardi Suardi; Nasrah Natsir; Untung Untung; Muhaemin B (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2026)
This study aims to describe tutors’ creativity in the learning process at PKBM Amanat Ummat by employingfourmainindicators:fluency,flexibility,originality,andelaboration.Theresearchused a qualitative approach with data collected through in-depthinterviews involving the head of the PKBM, tutors, and three adult learners as informants. Data analysis was conducted through data reduction, data display, and conclusion drawing, using source triangulation to ensure the validity of the findings. The results indicate that tutors demonstrated good creativity across all four indicators. In terms of fluency, tutors were able to deliver learning materials in a coherent, clear, and easily understandable manner. Regarding flexibility, tutors adapted their teaching methods to suit learners’ characteristics and adjusted their approaches when the previous methods were less effective. Originality was reflected in the use of personal experiences and local contexts, as well as the development of learning materials that were not merely copied from textbooks. Meanwhile, in elaboration, tutors organized learning materials systematically and explained concepts using concrete examples to strengthen learners’ understanding. Overall, the study shows that tutors at PKBM AmanatUmmat demonstrated a good level of creativity in supporting the learning process. Such creativity enhanced learner engagement, improved material comprehension, and fostered a contextual and enjoyable learning atmosphere.